Functional roles of FAP-α in metabolism, migration and invasion of human cancer cells - Mori, Noriko; Jin, Jiefu; Krishnamachary, Balaji; Mironchik, Yelena; Wildes, Flonné; Vesuna, Farhad; Barnett, James D.; Bhujwalla, Zaver M. (Frontiers in Oncology, 2023)
Fibroblast activation protein-α (FAP-α)c is a transmembrane serine protease that is attracting significant interest as it is expressed by a subgroup of cancer-associated fibroblasts that play a role in immune suppression and cancer metastasis. FAP-α is also expressed by some cancer cells, such as melanoma, colorectal and breast cancer cells. Triple negative breast cancer (TNBC) is an aggressive cancer that urgently requires identification of novel targets for therapy. To expand our understanding of the functional roles of FAP-α in TNBC we engineered a human TNBC cell line, MDA-MB-231, to stably overexpress FAP-α and characterized changes in metabolism by 1H magnetic resonance spectroscopy, cell proliferation, migration characterized by wound healing, and invasion. FAP-α overexpression resulted in significant alterations in myoinositol, choline metabolites, creatine, and taurine, as well as a significant increase of migration and invasion, although proliferation remained unaltered. The increase of migration and invasion are consistent with the known activities of FAP-α as an exopeptidase and endopeptidase/gelatinase/collagenase in tissue remodeling and repair, and in cell migration. We additionally determined the effects of FAP-α overexpression on the human fibrosarcoma HT1080 cell line that showed increased migration, accompanied by limited changes in metabolism that identified the dependency of the metabolic changes on cell type. These metabolic data identify a previously unknown role of FAP-α in modifying cancer cell metabolism in the TNBC cell line studied here that may provide new insights into its functional roles in cancer progression.